Etnomatematika: Masjid Soko Tunggal Dalam Pembelajaran Geometri 2D - Putra, Ryopanintama Yuniar; Wijayanto, Zainnur; Widodo, Sri Adi (Universitas Negeri Surabaya, 2020)
This research was conducted to find mathematical elements in the Soko Tunggal Mosque. The research method used in this study is a qualitative method with an ethnographic approach. The data used in this study were obtained from observations, documentation, and interviews. Observation and documentation are used to identify ethnomathematics in the Soko Tunggal Mosque, while documentation and interviews with the triangulation method to find out more deeply the cultural values that exist in the Soko Tunggal Mosque. From the results of the study found the concept of field geometry in the Soko Tunggal Mosque. Geometry elements identified include triangles, squares, rectangles, rhombus, circles and reflection. So that in learning mathematics on the material triangles, squares, rectangles, rhombus, circles, and reflection can use the context of a Soko Tunggal mosque.